Montenegro : Technical Assistance Report-Report on the Monetary and Financial Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance Report on Montenegro highlights work of the mission with the authorities which included compiling monetary data based on the IMF standardized report forms (SRF), 1SR, and SRF 2SR, for depository corporations. While the depository corporations sector currently dominates the financial system in Montenegro, the Central Bank of Montenegro (CBCG) should also ensure the availability of source data for the compilation and dissemination of a quarterly Other Financial Corporations (OFC) survey given the sector's potential to grow. The mission found the CBCG's current data collection framework is broadly appropriate for the compilation of monetary data in line with the MFSMCG 2016 for the depository corporations' sector, but further work is needed for OFCs. The mission advised on the correct treatment of negative interest accruals (due to negative interest rates) to ensure that the negative accruals diminish the value of the asset.